Twice differentiability of solutions to fully nonlinear parabolic equations near the boundary. (August 2020) - Adimurthi, Karthik; Banerjee, Agnid; Verma, Ram Baran
Abstract: In this paper, we prove H 2 + α regularity for viscosity solutions to non-convex fully nonlinear parabolic equations near the boundary. This constitutes the parabolic counterpart of a similar C 2, α regularity result due to Silvestre and Sirakov proved in [17] for solutions to non-convex fully nonlinear elliptic equations.